Influence of years of swim training on separate thoracoabdominal volumes during breathing - Silvatti, A. P.; Sarro, K. J.; Leite de Barros, R. M. (ISBS - Conference Proceedings Archive (Konstanz), 2007)
The purpose of this study was to verify the influence of the years of swim training on the separate thoracoabdominal volume variation during breathing using a kinematic analysis. Fifteen male swimmers were analyzed during tidal volume and vital capacity maneuvers. From the 3D coordinates of 30 markers fixed at the trunk the volumes of 4 separate compartments of the trunk (superior thorax, inferior thorax, superior abdomen and inferior abdomen) were calculated in function of time. During tidal volume, the coefficient of variation of the volumes of the superior and inferior abdomen increased with the years of swim training (p<0.05). These results suggest that the years of swim training affect the separate thoracoabdominal volumes reflecting the increased utilization of the diaphragm.